2020
DOI: 10.1016/j.parkreldis.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diffusion kurtosis changes in Parkinson's disease subtypes

Abstract: Background: Diffusion kurtosis imaging has been applied to evaluate white matter and basal ganglia microstructure in mixed Parkinson's disease (PD) groups with inconclusive results. Objectives: To evaluate specific patterns of kurtosis changes in PD and to assess the utility of diffusion imaging in differentiating between healthy subjects and cognitively normal PD, and between PD with and without mild cognitive impairment. Methods: Diffusion scans were obtained in 92 participants using 3T MRI. Differences in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, we found that PD-MCI can maintain attention; we speculate that the general slowness might be related to impairment of the intention system caused by a delay in motor system activation, as indicated by RT slowness being independent of the difficulty of the task. At the same time, this seems to be consistent with the results of Berman's study, indicating that the changes that occur in cognitively impaired PD are mostly driven by alterations in white matter integrity [23]. Furthermore, Yang et al demonstrated that despite no observed impairment in performance in behavioral attentional tasks, individuals with PD-MCI may have alterations in the attention functional network and present unique cerebellum and middle frontal gyrus activation as an effective compensatory mechanism for attentional tasks [24].…”
Section: Preliminary Datasupporting
confidence: 91%
“…However, we found that PD-MCI can maintain attention; we speculate that the general slowness might be related to impairment of the intention system caused by a delay in motor system activation, as indicated by RT slowness being independent of the difficulty of the task. At the same time, this seems to be consistent with the results of Berman's study, indicating that the changes that occur in cognitively impaired PD are mostly driven by alterations in white matter integrity [23]. Furthermore, Yang et al demonstrated that despite no observed impairment in performance in behavioral attentional tasks, individuals with PD-MCI may have alterations in the attention functional network and present unique cerebellum and middle frontal gyrus activation as an effective compensatory mechanism for attentional tasks [24].…”
Section: Preliminary Datasupporting
confidence: 91%
“…Results from our recent cross‐sectional human DKI study in PD patients with various phenotypes (with and without cognitive impairment and gross cortical brain atrophy) are in accord with the current findings thus further supporting the utility of DKI measures as a translational biomarker. In that study, increases of DKI parameters were present in cortical and subcortical brain regions engaged in the motor basal ganglia circuitry in the PD motor subtype with no cognitive deterioration or brain atrophy as compared to age‐matched healthy controls, whereas in the more malignant subtype with mild cognitive impairment (MCI) and frontal lobe atrophy, the DKI measures were not significantly different from those in healthy age‐matched controls (HC) (Minsterova et al., 2020).…”
Section: Discussionmentioning
confidence: 92%
“…However, the study also found opposite results, i.e., decrease in MK and FA in corpus callosum, cingulum, and inferior longitudinal fasciculus (Kamagata et al., 2014). Of note, Sejnoha‐Minsterova et al., (2020) reported decreases in MK and FA and increases in MD throughout the whole white matter skeleton only in patients with the malignant PD subtype with MCI and brain atrophy, while no differences were observed in the motor subtype as compared to HC (34). Unfortunately, we do not know much about white matter changes in our intragastric ROT mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no cure for PD, and the main treatment method is a combination of drugs and surgery. Stereotactic surgery is a method for the treatment of PD [ 10 ]. With the rapid development of imaging and neuroelectrophysiology, the use of brain stereotaxic technology to treat PD has become an important treatment method.…”
Section: Introductionmentioning
confidence: 99%